Indonesia Economic Quarterly, March 2011 : 2008 Again? - World Bank (Washington, DC, 2017)
The Indonesia economic quarterly reports on and synthesizes the past three months' key developments in Indonesia's economy. It places them in a longer-term and global context, and assesses the implications of these developments and other changes in policy for the outlook for Indonesia's economic and social welfare. Its coverage ranges from the macro economy to financial markets to indicators of human welfare and development. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged in Indonesia's evolving economy. Economic developments over the past quarter bear some strong similarities with the situation seen in the first half of 2008. Most notably, rises in domestic and international commodity prices have again brought with them a variety of risks, both positive and negative, at the macroeconomic and household level. While oil prices increased sharply with political developments in the Middle East and North Africa, strong price rises have been seen across global commodities. Non-energy commodities, including food, were up 30 percent in the six months to February 2011, similar to the increases seen in the first half of 2008. The experiences of other countries through the 2008 food price crisis suggest a range of potential policies which can provide well-targeted protection for vulnerable households and maintain and create incentives for producers to help limit future price volatility.